Evaluation of the Free Nutritious Meal Program in the 3T Region Areas Between Nutritional Equity and Infrastructure Challenges - Erlinawati, Noor Diah (Oshada, 2025)
This study aims to evaluate the effectiveness of the Free Nutritious Meal Program implemented in Indonesia’s frontier, outermost, and disadvantaged (3T) regions using a descriptive qualitative approach. The research focuses on three key dimensions: nutritional equity, infrastructural challenges, and community participation in sustaining program outcomes. Data were collected through the analysis of official policy documents, recent empirical studies, and relevant international literature. The findings indicate that although the program has improved access to nutritious food and public awareness of balanced diets, its implementation remains constrained by logistical barriers, weak intersectoral coordination, and limited human resource capacity at the regional level. Geographic isolation further exacerbates disparities in program effectiveness across regions. Nevertheless, evidence suggests emerging local innovations, including the utilization of local food resources, digital monitoring systems, and collaborative models involving communities and private sectors. The study concludes that achieving nutritional justice requires adaptive, participatory, and sustainable policy implementation that empowers local governance and community-based ownership. Strengthening these dimensions is essential for transforming national nutrition policy into an inclusive instrument for reducing inequality and promoting human development in Indonesia’s 3T regions.